Disilicon carbide (Si2C) in the interstellar medium - Sharma, M. K.; Chandra, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The Si2C and SiC2 both are considered to play key role in the formation of the SiC dust grains in the atmosphere of the carbon-rich stars. The molecule of our interest Si2C has been detected in the envelope of the red supergiant star IRC+10216 first time. It is an asymmetric top molecule having electric dipole moment of 1 Debye along the b-axis of inertia. Because of zero nuclear spin of both the Carbon and Silicon atoms, it has only paratransitions. Using the given spectroscopic data (rotational and centrifugal distortion constants and electric dipole moment), for the para-Si2C, we have calculated energies of 200 lower rotational levels (having energy up to 217.8 cm-1) and the Einstein A and B coefficients for 867 radiative transitions between the levels. We have solved a set of 200 statistical equilibrium equations coupled with 867 equations of radiative transfer (Sobolev analysis), where the collisional rate coefficients are taken from a scaling law. Out of 867 radiative transitions, 13 transitions have been found showing weak MASER action, and 19 transitions showing anomalous absorption. One transition 808-717 is found to show both the MASER action as well as the anomalous absorption. These transitions in addition to the observed transitions may play important role in the identification of Si2C in the cosmic objects. Принято считать, что Si2C и SiC2 играют ключевую роль в образовании пылинок SiC в атмосфере, богатых углеродом звезд. Молекула Si2C впервые была обнаружена в оболочке красного сверхгиганта IRC + 10216. Это молекула с асимметричным волчком, имеющая электрический дипольный момент 1 дебай вдоль оси инерции b. Из-за нулевого ядерного спина как атомов углерода, так и атомов кремния он имеет только парапереход. Используя приведенные спектроскопические данные (вращательные и центробежные константы дисторсии и электрический дипольный момент) для пара-Si2C, рассчитаны энергии 200 нижних вращательных уровней (имеющих энергию до 217.8 см-1) и коэффициенты Эйнштейна A и B для 867 радиационных переходов между уровнями. Решена система из 200 уравнений статистического равновесия в сочетании с 867 уравнениями переноса излучения (анализ Соболева), где коэффициенты частоты столкновений взяты из скейлингового закона. Из 867 радиационных переходов были обнаружены 3 перехода со слабым мазерным действием и 19 переходов с аномальным поглощением. Обнаружено, что один переход 808-717 демонстрирует как мазерное действие, так и аномальное поглощение. Эти переходы в дополнение к наблюдаемым переходам могут сыграть важную роль в идентификации Si2C в космических объектах.
Keywords: Astrophysics